Estimation of biocidal potential of desert phytopowders for the management of citrus canker - Atiq, Muhammad; Fatima, Kiran; Rajput, Nasir Ahmed; Sahi, Shahbaz Talib; Hameed, Akhtar; Usman, Muhammad; Ahmad, Usama; Sultan, Adeel; Iqbal, Shahid; Nawaz, Ahmad (Universiti Kebangsaan Malaysia, 2023)
Citrus is one of the most important fruit crops, throughout the world. It is a rich source of antioxidants and vitamin C. Citrus canker is a potential threat to its successful production. In current study, ten desert phytopowders including Xanthium strumarium, Dipterygium galucun, Leptadenia pyrotechnica, Haloxylon recurvum, Suaeda fruticosa, Salsola baryosma, Citrulus colocynthis, Abutilon indicum, Aerva javanica, and Calotropis procera at three different concentrations (5.0, 7.5 and 10.0%) were evaluated under in vitro conditions against Xanthomonas citri pv. citri. Among all phytopowders, X. strumarium and S. fruticosa, showed maximum inhibition zone (40 mm) followed by S. baryosma (38.50 mm) C. colocynthis (37 mm), Abutilon indicum (34 mm), H. recurvum (32 mm), D. galucun (30.5 mm), A. javanica, (29.50 mm), L. pyrotechnica, (29.5 mm) and C. procera (28 mm) as compared to control. Then, effective phytopowders were applied under greenhouse and field conditions @ 5.0, 7.5 and 10.0% against citrus canker. Combination of X. strumarium + S. baryosma showed minimum disease severity (22%) followed by X. strumarium (26%), X. strumarium + S. fruticosa (27%), S. fruticosa (27%), X. strumarium + S. baryosma (27%), and S. baryosma (29%) as compared to control. While in field experiment, the combination of X. strumarium + S. fruticosa showed significant results with minimum disease severity (32%) followed by S. fruticosa + S. baryosma (32%), X. strumarium + S. baryosma (33%), S. baryosma (35%), X. strumarium (36%) and S. fruticosa (36%) as compared to control. It is concluded that application of X. strumarium + S. baryosma phytopowders will be helpful for farmers to combat citrus canker.